Kv2 Ion Channels Determine the Expression and Localization of the Associated AMIGO-1 Cell Adhesion Molecule in Adult Brain Neurons - Bishop, Hannah I.; Cobb, Melanie M.; Kirmiz, Michael; Parajuli, Laxmi K.; Mandikian, Danielle; Philp, Ashleigh M.; Melnik, Mikhail; Kuja-Panula, Juha; Rauvala, Heikki; Shigemoto, Ryuichi; Murray, Karl D.; Trimmer, James S. (Frontiers in Molecular Neuroscience, 2018)
Voltage-gated K+ (Kv) channels play important roles in regulating neuronal excitability. Kv channels comprise four principal α subunits, and transmembrane and/or cytoplasmic auxiliary subunits that modify diverse aspects of channel function. AMIGO-1, which mediates homophilic cell adhesion underlying neurite outgrowth and fasciculation during development, has recently been shown to be an auxiliary subunit of adult brain Kv2.1-containing Kv channels. We show that AMIGO-1 is extensively colocalized with both Kv2.1 and its paralog Kv2.2 in brain neurons across diverse mammals, and that in adult brain, there is no apparent population of AMIGO-1 outside of that colocalized with these Kv2 α subunits. AMIGO-1 is co-clustered with Kv2 α subunits at specific plasma membrane (PM) sites associated with hypolemmal subsurface cisternae at neuronal ER:PM junctions. This distinct PM clustering of AMIGO-1 is not observed in brain neurons of mice lacking Kv2 α subunit expression. Moreover, in heterologous cells, coexpression of either Kv2.1 or Kv2.2 is sufficient to drive clustering of the otherwise uniformly expressed AMIGO-1. Kv2 α subunit coexpression also increases biosynthetic intracellular trafficking and PM expression of AMIGO-1 in heterologous cells, and analyses of Kv2.1 and Kv2.2 knockout mice show selective loss of AMIGO-1 expression and localization in neurons lacking the respective Kv2 α subunit. Together, these data suggest that in mammalian brain neurons, AMIGO-1 is exclusively associated with Kv2 α subunits, and that Kv2 α subunits are obligatory in determining the correct pattern of AMIGO-1 expression, PM trafficking and clustering.